Instead of the Editorial: Programme Group Safety and Security in Local Communities (2019–2024) – International and National Scientific and Professional Impact - Meško, Gorazd; Hacin, Rok (10. Nacionalna konferenca o varnosti v lokalnih skupnostih: Mirna, varna in inkluzivna družba ter varnost v lokalnih skupnostih, 2024)
The chapter presents selected activities of the program group in the field of publications in international scientific publications, the impact on the development of science and practice in Slovenia, connecting with the international research and professional environment, and performing various activities in the field of scientific associations, international and European organizations, as well as working on editorial boards and reviewing international scientific journals in the period 2019–2024. The findings of the review of the publicly available database SICRIS show that the members of the program group have done a lot of quality work by presenting research in international publications, organizing national conferences on security in local communities, appearing in the media, and trying to raise the quality of practice in the field of security in local environments.